The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jcpe.13247
|View full text |Cite
|
Sign up to set email alerts
|

Injectable platelet‐rich fibrin and microneedling for gingival augmentation in thin periodontal phenotype: A randomized controlled clinical trial

Abstract: Aim The aim of this present study was to evaluate the effect of gingival thickness (GT) and keratinized tissue width (KTW) using injectable platelet‐rich fibrin (i‐PRF) alone and with microneedling (MN) in individuals with thin periodontal phenotypes. Materials and Methods In this split‐mouth study, 33 systemically healthy patients with thin periodontal phenotypes were randomly treated with MN + i‐PRF and i‐PRF. I‐PRF was injected on one side, and MN + i‐PRF was performed on the other side of the same patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 40 publications
0
50
0
1
Order By: Relevance
“…22,23 Platelets and cytokines become trapped within the i-PRF fibrin matrix after injection leading to a slow and gradual release of growth factors over time. 19 Use of this injectable form of PRF has been reported for the treatment of various oral and maxillofacial procedures 24,25 and alopecia. 26 Limited data have been reported for its use in aesthetic skin rejuvenation.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Platelets and cytokines become trapped within the i-PRF fibrin matrix after injection leading to a slow and gradual release of growth factors over time. 19 Use of this injectable form of PRF has been reported for the treatment of various oral and maxillofacial procedures 24,25 and alopecia. 26 Limited data have been reported for its use in aesthetic skin rejuvenation.…”
Section: Introductionmentioning
confidence: 99%
“…The combination has shown benefits, such as improved angiogenesis and handling ability by combining the small bone granules into a bulk material to use in bone grafting surgery [ 9 , 10 , 11 ]. Further use of i-PRF demonstrated that it was effective in regaining gingival thickness, reducing periodontal pocket depth, and attachment loss in periodontal tissue regeneration [ 12 , 13 ]. Although a few cases have reported an encouraging outcome, there has been a paradigm shift concerning the use of i-PRF in clinical bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The use of microneedles independently or with grafting procedures, based on the principle of accelerated wound healing, could potentially improve the areas with thin gingival biotype. Ozsagir et al performed a clinical study where they successfully used injectable platelet-rich fibrin (I-PRF) with microneedles to enhance gingival biotype and keratinized gingiva 12 .…”
Section: Current and Prospective Applications In Dentistrymentioning
confidence: 99%